Transaminase encoded by NCgl2515 gene of Corynebacterium glutamicum ATCC13032 is involved in γ-aminobutyric acid decomposition. (April 2017) - Shi, Feng; Si, Han; Ni, Yalan; Zhang, Lei; Li, Yongfu
Graphical abstract: Highlights: NCgl2515 gene encodes weak γ-aminobutyric acid (GABA) transaminase in C. glutamicum . Deletion of NCgl2515 and gabT can prevent GABA from decomposing. NCgl2515 protein uses both α-ketoglutarate and pyruvate as the amino acceptor. NCgl2515 and GabD conduct GABA metabolism only at neutral to alkaline conditions. Abstract: Corynebacterium glutamicum that expresses an exogenousl -glutamate decarboxylase (GAD) gene can synthesize γ-aminobutyric acid (GABA). GABA is decomposed to succinic semialdehyde (SSA) by GABA transaminase (GABA-T) and to succinate thereafter by SSA dehydrogenase (SSADH). However, deletion of the gabT gene encoding GABA-T could not prevent GABA from decomposing at neutral pH. In this study, an additional transaminase gene, NCgl2515, was deleted in a gabT -deleted GAD strain, and GABA fermentation in this gabT NCgl2515-deleted GAD strain was investigated. GABA concentration remained at 22.5–24.0 g/L when pH was maintained at 7.5–8.0, demonstrating that GABA decomposition was reduced. Activity assay indicated that unlike GabT, which exhibits high GABA-T activity (1.34 ± 0.06 U/mg) and utilizes only α-ketoglutarate as amino acceptor, the purified NCgl2515 protein exhibits very low GABA-T activity (approximately 0.03 U/mg) only when coupled with the SSADH, GabD, but can utilize both α-ketoglutarate and pyruvate as amino acceptor. The optimum pH for coupled NCgl2515–GabD was 8.0, similar to that of GabT (7.8). Therefore, NCgl2515 has weak GABA-T activity and is involved in GABA decomposition in C. glutamicum . Deletion of gabT and NCgl2515 could effectively reduce GABA decomposition at neutral pH.